Perkembangan Fungsi dan Pertunjukan Tradisi Kuda Renggong di Sumedang Utara - Memed Ruswandi (Pascasarjana ISBI Bandung, 2017)
Kuda Renggong is an art growing and developing from Sumedang regency which has function as ritual means of circumsicion, gusaran, and welcoming guests. Nowadays, the functions also develop as entertainment in the context of circumsicion party, welcoming guests, birthday, and festival. The performance of Kuda Renggong contains the elements of music, dance, and costumes. This study is about the changing of the community and the culture toward the tradition of Kuda Renggong arts in North Sumedang. Diachronically, the analysis is based on the interviews to the players/performers of Kuda Renggong from the youngest to the oldest, penanggap (the host inviting or paying for the performance), the community fgure, and the spectators. The changes are shown on the musical instruments, costumes, the dancers atraction, and the technology. Besides, it is now also supported by the city community. In other words, Kuda Renggong is in?uential to the changing of the culture and the people.Keywords: development, function, society, Kuda Renggong